2016
DOI: 10.1111/jpy.12479
|View full text |Cite
|
Sign up to set email alerts
|

The variable routes of rafting: stranding dynamics of floating bull kelp Durvillaea antarctica (Fucales, Phaeophyceae) on beaches in the SE Pacific

Abstract: Dispersal on floating seaweeds depends on availability, viability, and trajectories of the rafts. In the southern hemisphere, the bull kelp Durvillaea antarctica is one of the most common floating seaweeds, but phylogeographic studies had shown low connectivity between populations from continental Chile, which could be due to limitations in local supply and dispersal of floating kelps. To test this hypothesis, the spatiotemporal dynamics of kelp strandings were examined in four biogeographic districts along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 75 publications
2
34
0
Order By: Relevance
“…D. antarctica in Chile experiences competition from other algal species including Lessonia spp. towards its northern latitudinal range limit, reducing its density and prevalence, but is more abundant toward the south (Santelices et al 1980), where abundant rafting populations of large adult plants have also been observed (López et al 2017a). In this research, we sampled southward from the northern range limits of Durvillaea in Chile and Australia, such that more southern populations also had higher host densities, which could have led to increased pathogen transmission, and thus infection levels, at high latitudes.…”
Section: Population Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…D. antarctica in Chile experiences competition from other algal species including Lessonia spp. towards its northern latitudinal range limit, reducing its density and prevalence, but is more abundant toward the south (Santelices et al 1980), where abundant rafting populations of large adult plants have also been observed (López et al 2017a). In this research, we sampled southward from the northern range limits of Durvillaea in Chile and Australia, such that more southern populations also had higher host densities, which could have led to increased pathogen transmission, and thus infection levels, at high latitudes.…”
Section: Population Densitiesmentioning
confidence: 99%
“…For each complete kelp individual (including holdfast and fronds), the presence of galls of Maullinia was determined, and the frequency of infected specimens was calculated. The details of the sampling protocols used for collection and measurement of stranded specimens of D. antarctica are described in López et al (2017a).…”
Section: Sample Collectionmentioning
confidence: 99%
“…This study was conducted on 33 sandy and pebble/cobble beaches (28° S–42° S) across the benthic and pelagic geographic range of D. antarctica (Figure ). Distances between adjacent beaches varied from 30 to 100 km and the extension of the stretches that were surveyed on each beach ranged from 0.28 to 11.08 km, depending on beach length and/or amounts of stranded bull kelps (for details see López et al., ). Beaches were distributed across the four biogeographic districts, based on Camus () and a previous study (López et al., ): the southern edge of the Peruvian Province, 28° S–30° S, hereafter termed Coquimbo‐Choros District (CCD); Septentrional District (SED), 30° S–33° S; Mediterranean District (MED), 33° S–37° S; Meridional District (MD), 37° S–42° S (Figure , see also Supporting Information Tables S1.1 and S1.2).…”
Section: Methodsmentioning
confidence: 99%
“…Rafts of D. antarctica frequently wash up on sandy beaches within its geographic range (Duarte, Jaramillo, Contreras, Acuña, & Navarro, ), and stranded biomass tends to vary strongly among biogeographic districts (López, Macaya, Tala, Tellier, & Thiel, ), being highest in the northern‐central (30° S–33° S) and southernmost districts (37° S–42° S). Stranded specimens are also frequently found outside their northern geographic limit (<30° S), showing indications of prolonged floating times (López et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation